Pemanfaatan Media Digital dalam Pembelajaran IPA untuk Meningkatkan Keterlibatan Siswa Sekolah Dasar - Novaria Lailatul Jannah; Lailatul Mufidah; Zelika Jauza Bilqis Setyawan; Ika Putri Rahayu (MODELING: Jurnal Program Studi PGMI, 2025)
Student engagement is a crucial aspect of elementary school learning, yet in practice, participation levels are often low throughout the learning process. The use of digital media is seen as a potential pedagogical strategy to increase active student engagement. This study aims to examine the effect of digital media use in science learning on elementary school student engagement. The study used a quantitative approach with a quasi-experimental non-equivalent control group design. The subjects consisted of fifth-grade students divided into an experimental class and a control class. The research instrument was a student engagement questionnaire covering cognitive, affective, and psychomotor dimensions, supported by observation sheets. Data were analyzed using descriptive and inferential statistics. The results showed that the average student engagement score in the experimental class increased from 55.00 in the pretest to 85.00 in the posttest, while in the control class it increased from 50.00 to 65.00. The increase in student engagement in the experimental class occurred across all dimensions of engagement, with the highest increases in the psychomotor and cognitive dimensions. The prerequisite test results showed normally distributed and homogeneous data, while the mean difference test indicated a significant difference in student engagement between the experimental and control classes (p < 0.05). Based on these findings, it can be concluded that the use of digital media in science learning has a positive and significant effect on increasing elementary school student engagement. Therefore, it is recommended that digital media be pedagogically integrated into science learning to create more interactive, meaningful, and student-centered learning in the digital age.